Change in traffic volumes in construction work zones - Roman Rohalskyy; Romana Bura (Transport Technologies)
The problem of bottlenecks on the road network is relevant, especially in cities with radial and radial-ring schemes, since in case of their occurrence on arterial radial streets, it is difficult to choose an alternative route due to the low capacity of secondary streets. One of these bottlenecks is the repair work area, where, due to the closure of one street, the detour is carried out by parallel routes, which increases the load on local streets and driveways. Traffic flow volumes in the repair work areas are investigated in this paper. A site was selected where repairs were carried out in 2023. A citywide street of signalized traffic was closed due to repair work. The authors have forecasted the volumes of traffic flow that will be moving. After the start of the repair work, the actual traffic volume was determined by field surveys. The research was conducted over three months. The results showed that in the first week, the volumes were 2% higher than predicted; in the second week, they corresponded to the predicted values, and starting from the third week, they began to decrease. Approximately the same volumes were observed between the seventh and twelfth weeks of the study. They were 18% lower than forecasted at the beginning of the study. Since the research results showed that drivers need about a month to choose an alternative route to bypass the most congested sections of the road network, a recommendation was made to install road signs informing about the detour a month before the start of the repair work. In our opinion, this recommendation will allow drivers to plan and choose an alternative detour route in advance so that the detour section is less congested at the beginning of the repair work.